Authoritarian Governance and Ambiguous Religious Policy: An Uncertain Future for Covenantal Pluralism in Tajikistan - Epkenhans, Tim (The review of faith & international affairs, 2021)
The former Soviet Central Asian republic of Tajikistan has witnessed a conflictual political and social transformation after 1991 leading to a devastating civil war between 1992 and 1997. After the civil war, international efforts of liberal peacebuilding and post-conflict rehabilitation allowed a domestic détente, in which political and, importantly, religious pluralism could flourish unprecedently for the standards of the country. Still, this form of pluralism did not meet the ideal standards of covenantal pluralism as such. In the past decade, moreover, Tajikistan has gradually turned into a consolidated autocracy in which even formal pluralism is suspended. Authoritarian governance, especially in the sphere of religion, has aggravated societal divides and undermined social cohesion in the country. Although the short-term prospects for pluralism in general and covenantal pluralism in particular are dim, a differentiated perspective on the ideal of covenantal pluralism in the longue durée might provide possible starting points for meaningful engagement in Tajikistan bridging religious, societal, and political divides.